Trends and models of humanized nursing care in the neonatal intensive care unit: A narrative review - Tello Correa, Gladys; Huertas Angulo, Flor; Ramírez García, Esther (Horizonte Sanitario, 2026)
Objective: To synthesize recent scientific evidence on trends and models of humanized nursing care in Neonatal Intensive Care Units (NICU). Materials and Methods: A narrative literature review was conducted. The search was performed in the PubMed, Scopus, and BVS databases for the period 2020-2025, including studies in Spanish, English, and Portuguese. The process of identifying and selecting articles followed the PRISMA guidelines. The research question was structured using the PICO acronym. The methodological quality of the studies was assessed using the Critical Appraisal Skills Programme (CASP) checklists. After a rigorous screening and evaluation process, 12 articles were selected for qualitative synthesis. Results: Four trends and models that define humanized care were identified: 1) Ethical leadership in technological innovation, prioritizing dignity over technological advancement; 2) Family-Centered Care (FCC) and parental empowerment, which demonstrates clinical benefits for newborns; 3) Extension of care to a holistic and spiritual approach, essential in grief care; and 4) Adoption of digital trends, including telehealth nursing, to ensure continuity of family support. Conclusions: Trends in humanized care are essential for the quality of neonatal survival. Current nursing practice is oriented toward comprehensive care and family empowerment, achieving an ethical transformation of the professional role. It is imperative to standardize these trends and models to guarantee more humane and effective care in the NICU. Keywords: Humanized Care; Neonatal Intensive Care Units; Neonatal Nursing; Family Centered Care; Trends.